2005
DOI: 10.1523/jneurosci.2638-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent and Selective Impairment of Long-Term Potentiation in the Anterior Piriform Cortex of Mice Lacking the Fragile X Mental Retardation Protein

Abstract: Synaptic function and plasticity were studied in mice lacking the fragile X mental retardation protein (FMRP), a model for the fragile X mental retardation syndrome. Associational connections were studied in slices of anterior piriform (olfactory) cortex, and Schaffercommissural synapses were studied in slices of hippocampus. Knock-out (KO) mice lacking FMRP were compared with congenic C57BL/6J wild-type (WT) controls. Input-output curves and paired-pulse plasticity were not significantly altered in KO compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 62 publications
6
115
1
1
Order By: Relevance
“…Although it is consistently reported that LTD is exaggerated in hippocampus (Huber et al, 2002;Zhang et al, 2009) and cerebellum (Koekkoek et al, 2005), LTP impairment depends on the region of the brain as well as the induction protocols. Some reports find that LTP is not affected in the hippocampus (Bear et al, 2004;Godfraind et al, 1996;Paradee et al, 1999;Zhang et al, 2009), whereas others show that LTP is reduced in the hippocampus (Hu et al, 2008;Larson et al, 2005;Lauterborn et al, 2007;Lee et al, 2011;Shang et al, 2009). In the ACC, we reported that the early phase of LTP was impaired in cingulate pyramidal cells (Zhao et al, 2005a).…”
Section: Fmr1 Ko Mice Exhibited Reduced L-ltp In the Accmentioning
confidence: 63%
“…Although it is consistently reported that LTD is exaggerated in hippocampus (Huber et al, 2002;Zhang et al, 2009) and cerebellum (Koekkoek et al, 2005), LTP impairment depends on the region of the brain as well as the induction protocols. Some reports find that LTP is not affected in the hippocampus (Bear et al, 2004;Godfraind et al, 1996;Paradee et al, 1999;Zhang et al, 2009), whereas others show that LTP is reduced in the hippocampus (Hu et al, 2008;Larson et al, 2005;Lauterborn et al, 2007;Lee et al, 2011;Shang et al, 2009). In the ACC, we reported that the early phase of LTP was impaired in cingulate pyramidal cells (Zhao et al, 2005a).…”
Section: Fmr1 Ko Mice Exhibited Reduced L-ltp In the Accmentioning
confidence: 63%
“…2A). To further analyze this apparent contradiction of the mGluR theory in the amygdala, we took note of earlier findings from other brain areas of Fmr1 KO mice exhibiting deficient forms of LTP that are not necessarily dependent on mGluR5 (7,10,11,15,16). Because restoration of AMPARs to the surface could also be mediated by other nonmGluR plasticity mechanisms, we wanted to ensure that contributions from such mechanisms are not constrained by our use of the 30 Hz mGluR-LTP induction protocol alone.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying basis for this enhanced hippocampal mGluR-LTD is abnormally high internalization of the AMPA receptor (AMPAR) subunit, GluR1, caused by the absence of the endpoint inhibition normally provided by FMRP (2,6). Interestingly, defective AMPAR-mediated plasticity has also emerged as a common phenotype in other brain areas in the Fmr1 KO mouse, including the cortex and cerebellum (7)(8)(9)(10)(11). However, such deficits are not limited to LTD, but are also frequently manifested as an impairment of long-term potentiation (LTP) (7,(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Several studies have also shown impaired long-term potentiation (LTP) in different cortical areas of Fmr1 KO mice Zhao et al, 2005;Desai et al, 2006). In contrast, LTP appeared to be normal in the Fmr1 KO hippocampus (Paradee et al, 1999;Li et al, 2002;Larson et al, 2005). However, a defect in hippocampal LTP could be detected at lower levels of stimulation (Lauterborn et al, 2007), which was in line with another study showing that spike-timing-dependent LTP in the Fmr1 KO cortex was normal after a strong stimulus, but impaired when using a threshold induction paradigm (Meredith et al, 2007).…”
Section: Altered Synaptic Plasticity In Fmr1 Ko Micementioning
confidence: 99%